High Reusability of NiAl LDH/Biochar Composite in the Removal Methylene Blue from Aqueous Solution - Aldes Lesbani; Neza Rahayu Palapa; Rabelia Juladika Sayeri; Tarmizi Taher; Nurlisa Hidayati (Universitas Gadjah Mada, 2021)
Ni/Al layered double hydroxide was used as a starting material for composite formation with biochar as a matrix. The materials were characterized using X-ray, FTIR, nitrogen adsorption-desorption, thermal, and morphology analyses. The NiAl LDH/Biochar material is then used as an adsorbent of methylene blue from an aqueous solution. The factor that was influencing adsorption such as pH, time, methylene blue concentration, and temperature adsorption was studied systematically. The regeneration of adsorbent was performed to know the stability of NiAl LDH/Biochar under several cycle adsorption processes. The results showed that NiAl LDH/Biochar has a specific diffraction peak at 11.63° and 22.30°. NiAl LDH/Biochar has more than ten-fold surface area properties (438,942 m2/g) than biochar (50.936 m2/g), and Ni/Al layered double hydroxide (92.682 m2/g). The methylene blue adsorption on NiAl LDH/Biochar follows a pseudo-second-order kinetic adsorption model and classify as physical adsorption. The high reusability properties were found for NiAl LDH/Biochar, which was largely different from biochar and Ni/Al layered double hydroxide.